Addressing the Failure of Abstinence-only Sex Education Programs: An Emerging Leadership Perspective - Cedric Harville II (Florida Public Health Review, 2012)
Over the past 15 years, abstinence-only sex education has been the sole method of education supported by the federal government as it relates to adolescent sexual health. Despite the exponential increase offunding provided for abstinence-only sex education, few tangible positive results have surfaced. At high rates, teens still take part in risky sexual behaviors, and are at high risks for teen pregnancy, sexually transmitted diseases, and HIV/AIDS. As a result, it is necessary to take an alternative approach that provides adolescents with a comprehensive view of sex education in order to effectively reduce these negative outcomes. A comprehensive education will provide adolescents with the adequate knowledge about contraception, how to protect themselves, and the consequences of sexual activity, so they may be able to make informed and educated decisions about sex. This one-sided abstinence-only approach is an archaic view that needs to be changed by our state and federal legislators, and school administrators, so adolescents are prepared to lead healthy lives.